Talking trees and prattling plants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
It used to be said that the gardeners who got the best results from their plants did so by talking to them. Now it seems that the plants can 'talk' back and tell you their needs! When plants draw up water, their cells are like millions of tiny...